CHAPTER 6 'IN SITU' DISSOLUTION OF HEAVY MINERALS THROUGH EXTREME WEATHERING, AND THE APPLICATION OF THE SURVIVING ASSEMBLAGES AND THEIR DISSOLUTION CHARACTERISTICS TO CORRELATION OF DUTCH AND GERMAN SILVER SANDS - Loon A.J.(T.) V.; Mange M.A. (My University, 2007)
Diverse processes during the sedimentary cycle may generate heavy mineral associations that are devoid of clear signatures of the source region, especially in sediments that experienced unusually severe environmental conditions, and thus their provenance reconstruction becomes problematical. This study provides a new insight into the impact of 'in situ' weathering on heavy mineral assemblages, rarely dealt with in recent years, by evaluating the effects of extreme weathering that imparted an unusual bulk and heavy mineral composition to the Tertiary Dutch and German 'silver sands' (sands that consist almost exclusively of quartz). Specific findings of our heavy mineral study of these silver sands include: (1) tourmaline can be strongly weathered; (2) the chemical weathering of tourmaline is colour-related and therefore depends probably on its particular chemistry; (3) staurolite is a reliable indicator of the degree of chemical weathering; (4) the effects of extreme chemical weathering on a heavy mineral assemblage differ fundamentally from those of burial diagenesis as, for example, in the total disappearance of apatite; (5) the joint occurrence of fresh and strongly weathered grains (with the same chemical composition) of one heavy mineral species indicates that the degree of chemical weathering is a statistical rather than a fixed parameter; (6) no heavy mineral analysis is reliable if the degree and the effects of in situ weathering are not taken into account; (7) a reliable analysis of extremely weathered sediments requires sand samples of several kilograms. Although regional or local differences in weathering may obscure original heavy mineral compositions and thus impede subdivision of, and correlation between, sedimentary units, understanding the end-products of in situ weathering may also be helpful in drawing stratigraphic boundaries between units with originally comparable heavy mineral compositions, as is proven for the silver sands. © 2007 Elsevier B.V. All rights reserved.
Keywords: GRAIN CHARACTERISTICS; HEAVY MINERAL DISSOLUTION; IN SITU WEATHERING; SILVER SANDS; STAUROLITE WEATHERING; STRATIGRAPHIC CORRELATION; TOURMALINE COLOUR VARIETIES